Evidence of unconscious motor adaptation to cognitive and auditory distraction. (October 2013) - Berg, William P; Dessecker, Dirk J
Using a simulated driving station, 36 participants applied the brake as quickly as possible following the activation of a red light under each of six conditions including (1) the control (braking only), (2) 72 dBA music stimulus, (3) 86 dBA music stimulus, (4) cell phone conversation, (5) cell phone conversation and 72dBA music, and (6) cell phone conversation and 86dBA music. Participants were distracted by the cell phone conversation, as demonstrated by slower response time and reaction time (RT). The addition of the music stimulus, even at 86 dBA, did not exacerbate the deficits. Braking movement time was faster, and peak braking force greater when the cell phone conversation was present than when it was absent. Participants appear to have anticipated impaired RT and adapted unconsciously by executing a more rapid movement to the brake pedal. Also, participants appear to have compensated for slower RT by applying greater braking force. The adaptive behavior observed in the experiment is discussed in the context of unconscious goal pursuit and neuromotor noise theory.